Comparing Different Light Models for Virtual Electrodes in Optoelectronic Tweezers - Guzman‐Saleh, Ernesto; Perez‐Gonzalez, Victor H.; Martinez‐Duarte, Rodrigo (Electrophoresis, 2025)
ABSTRACT Optoelectronic tweezers (OET) allow for the physical manipulation of particles of interest via dielectrophoresis (DEP) in microfluidic devices. To produce the nonuniform electric field required to enable DEP, light is used to expose a photoconductive film and create a so‐called virtual electrode (VE). Several attempts have been made to model the light profile used to excite the photoconductive layer and produce the VE. However, no comparison of the models has been presented in the literature. Here, we present a comparative study among the rectangular, Gaussian, and saturated‐Gaussian models in mapping to light profiles obtained experimentally. These models were then used to predict the activation of a VE and the distribution of the electric field in an OET system. From this comparison, it is possible to conclude that the saturated‐Gaussian model should be the preferred choice to study these systems. Moreover, VEs were also compared numerically to conventional gold electrodes used regularly in DEP applications, concluding that very relevant differences exist between the electric fields produced by these two types of electrodes.